DEVELOPMENT OF CHITOSAN MODIFIED POLYURETHANE COMPOSITE AS A BASE MATERIAL FOR ANTIBACTERIAL COATING PAINT - Wahyuni, Sri; Rihayat, Teuku; Syafruddin, S (Politeknik Negeri Lhokseumawe, 2023)
ABSTRACTPolyurethanes are generally made from petroleum-based polyols, but the current state of petroleum is depleting. The availability of petroleum, which is currently decreasing, encourages other parties to look for new alternatives. One alternative that can be used is palm oil. Technological developments that continue to increase are now also a reference for the development of antibacterial polyurethane coating paints which are carried out by adding another filler, namely chitosan. This study aims to determine the effect of variations in the weight of chitosan as an antibacterial agent and to determine the effect of the ratio of polyol and TDI on the quality of the paint analyzed through functional group analysis with Fourier Transform Infra Red (FTIR), morphological analysis of Surface Scanning Electron Microscopy (SEM), Heat resistance test with Thermo Gravimetry Analyzer (TGA), and Bacterial activity test. The analysis process was carried out with variations in the weight of chitosan (0; 2; 3; 4; 5; 6) % w/w and variations in the ratio of polyol and TDI (50:50) %; (40:60)%; (45:55)%. The test results showed that the best polyurethane paint was the variation in the ratio of polyol and TDI 50:50% with 6%w/w chitosan filling. This is because the more chitosan added, the better it will be in inhibiting bacterial activity, and the more polyols, the better the paint quality. The test results showed that the best polyurethane paint was the variation in the ratio of polyol and TDI 50:50% with 6%w/w chitosan filling. This is because the more chitosan added, the better it will be in inhibiting bacterial activity, and the more polyols, the better the paint quality. The test results showed that the best polyurethane paint was the variation in the ratio of polyol and TDI 50:50% with 6%w/w chitosan filling. This is because the more chitosan added, the better it will be in inhibiting bacterial activity, and the more polyols, the better the paint quality.Keywords: Chitosan, Composites, Polyols, Polyurethanes, TDI